Thrombocyte-derived Dickkopf1 promotes macrophage polarization in the Bleomycin-induced lung injury model - Sung, Eun-Ah; Park, Min Hee; Song, SuJeong; Alanya, Hasan; Henegariu, Octavian; Liu, Jinze; Erson-Omay, E Zeynep; Sime, Patricia J.; Chae, Wook-Jin (Frontiers in Immunology, 2023)
Immune responses are crucial to maintaining tissue homeostasis upon tissue injury. Upon various types of challenges, macrophages play a central role in regulating inflammation and tissue repair processes. While an immunomodulatory role of Wnt antagonist Dickkopf1 (DKK1) has been implicated, the role of Wnt antagonist DKK1 in regulating macrophage polarization in inflammation and the tissue repair process remains elusive. Here we found that DKK1 induces gene expression profiles to promote inflammation and tissue repair in macrophages. Importantly, DKK1 induced various genes, including inflammation and tissue repair, via JNK (c-jun N-terminal kinase) in macrophages. Furthermore, DKK1 potentiated IL-13-mediated macrophage polarization and activation. The co-inhibition of JNK and STAT6 markedly decreased gene expressions relevant to inflammation and fibrosis by DKK1 and IL-13. Interestingly, thrombocyte-specific deletion of DKK1 in mice reduced collagen deposition and decreased Arg1, CD206, HIF1α, and IL1β protein expressions in monocyte-derived alveolar macrophages in the acute sterile bleomycin (BLM)-induced lung injury model. These data suggested that thrombocytes communicate with macrophages via DKK1 to orchestrate inflammation and repair in this model. Taken together, our study demonstrates DKK1’s role as an important regulatory ligand for macrophage polarization in the injury-induced inflammation and repair process in the lung.